The Organisation of Synods of Competitors in the Roman Empire - Bram Fauconnier (Historia, 2017)
According to Decker, the function of archigrammateus corresponds to a higher function of the synod in Rome, whereas the office of grammateus is a local one in relation to the synod's activities in Naples.77 This matches the finding that the high officials in Rome claimed to represent the ... How would it not have been equally illogical if the archons of the musical artists ... also demanded to receive a hundredth from the athletes?" In the light of the above, Hadrian probably did not use the word 'archons', which he juxtaposes to the xystarchs, as a broad, general term for any official. Since he wrote to the thymelic synod itself, he must have referred to the synod's archons who were active all over the empire: our three-headed group of first archon, archon grammateus and archon nomodeiktes. [...]the term can be seen as a marker of the high status of the officials in Rome. 40 Cf. the certificate of the boxer Hermeinos: P. Lond. 3 1178, l. 50-58. [...]the fact that another inscription with the name of the thymelic synod (IG XIV 2500) was found in the temple of Diana itself seems decisive. 48 I. Ephesos 22; Milet VI 3 1140, mentioning a high priest of the ...; Sardis VII 1 13, l. 10, where Robert 1975: 169 (note 79) restores ...